The role of abnormal subaortic morphometry as a substrate for left ventricular outflow tract obstruction following atrioventricular septal defect repair. (22nd September 2021) - Chandiramani, Ashwini Suresh; Bader, Vivian; Finlay, Emma; Lilley, Stuart; McLean, Andrew; Peng, Ed
Abstract:  : OBJECTIVES: Although left ventricular outflow tract (LVOT) obstruction is a recognized risk after atrioventricular (AV) septal defect (AVSD) repair, quantitative assessments to define the substrate of the obstruction are lacking. METHODS: Morphometric analyses were based on measurements from early 2-dimensional echocardiographic scans (within 3 months postoperatively) for 117 patients (82 CAVVO = common AV valve; 35 SAVVO = separate AV valve orifices), which were compared to 50 age/weight matched controls (atrial septal defect/ventricular septal defect). Late echocardiographic analyses were performed in 57 patients with AVSD (follow-up range, 1.2–10.7 years). RESULTS: Adequate z scores (above −2.5) were observed in 109 (93%) patients with AVSD at the aortic annulus and in 89 (76%) with AVSD in the subaortic area. Compared to the control group, patients with AVSD had lower median z scores at the aortic annulus (−0.64 vs 0.60; P  < 0.001) and the subaortic areas (−1.48 vs 0.59; P  < 0.001), disproportionate subaortic/aortic annulus ratio <1.00 (67% vs 22%; P  < 0.001), narrower annuloaortic-septal angle (94.0 vs 104.0; P  < 0.001) and annuloaortic left AV valve angle (78.0 vs 90.0; P  < 0.001). Compared to patients with CAVVO, those with SAVVO had narrower annuloaortic-septal angles ( P  = 0.022) that persisted at late analysis, with lower subaortic/aortic annular ratios ( P  = 0.039). In patients with CAVVO, lower early postoperative subaortic z scores were found following modified single-patch repairs (median −2.12 vs −1.02 in two-patch repairs; P  = 0.004). A total of 6/117 (5%) patients (4 CAVVO, 5% and 2 SAVVO, 6%) required reoperations for LVOT obstruction (mean 6.9 years postoperatively), with no difference in morphology or types of operations. CONCLUSIONS: Despite having adequate z scores, patients with AVSD demonstrated abnormal LVOT morphometrics early postoperatively. Besides intrinsic morphology, repair techniques may have an impact on postoperative LVOT morphometrics and requires further evaluation. Abstract : Atrioventricular septal defect (AVSD) comprises a spectrum of congenital heart diseases characterized by a common atrioventricular (AV) junction and a deficient AV septum.